GUARANTEES OF LABOR RIGHTS IN UZBEKISTAN AS ONE OF THE PRINCIPLES OF DECENT WORK (International scientific-electronic journal “Pioneering studies and theories”, 2025)
The article examines the main guarantees of labor rights in Uzbekistan as one of the key principles of decent work. The legislative framework is analyzed, including the Constitution, the Labor Code of the Republic of Uzbekistan, ratified conventions of the International Labor Organization and other regulatory legal acts. Particular attention is paid to mechanisms for ensuring the right to work, employment, fair wages, safe working conditions and social protection. The role of trade unions and social dialogue in achieving decent work is also considered. The conclusion notes the prospects for improving labor legislation and strengthening control over its observance.